The political purge of Victoriano Taibo - Méixome, Carlos (Historia y Memoria de la Educación, 2022)
This study deals with the political purge of Victoriano Taibo García (1885-1966), a poet and narrator in the Galician tongue and one of the signatories of the « Manifesto Nacionalista» during the first assembly of As Irmandades da Fala (IF) in 1918. Our work is based on the dossier kept in the Archivo General de la Administración (AGA), in Alcalá de Henares; on his collection of letters, that is part of his personal archive, kept in the Instituto de Estudos Miñoráns (IEM); on the documentation regarding municipal plenary sessions in the archive of Gondomar (AMG); and on other detailed sources that are cited. Taibo García was a cultural activist and teacher in several schools in Galicia. Shortly before the proclamation of the II Republic, as an already renowned poet, he was appointed to the school of Morgadáns, a civil parish of Gondomar (Pontevedra), , where he taught for almost two decades and forged a strong bond to the area. He was never affiliated with the Partido Galeguista (PG), despite his being committment to Galicianism. After the military uprising, he was not punished immediately, but, in the purge that followed, was sanctioned with banishment to Villalar de los Comuneros (Valladolid), from January of 1938 to the same month of 1942. In 1948 he was accepted into the Real Academia Galega (RAG) and gave a speech on Rosalía de Castro. He died in 1966.